An iron-nitrogen co-doped carbon material catalyst and its application in the synthesis of quinazoline and its derivatives
By using iron-nitrogen co-doped carbon material catalyst, the problems of low catalytic efficiency and poor selectivity in the existing quinazoline synthesis methods are solved, and the efficient and highly selective synthesis of quinazoline and its derivatives are achieved, with stability and Good reusability has expanded the selectivity of raw materials.
Patent Information
- Application Number
- CN202210734735.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-27
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-06-27
AI Technical Summary
The existing synthesis methods of quinazoline and its derivatives have low catalytic efficiency, poor selectivity, harsh reaction conditions, high cost and poor substrate tolerance, which limits the efficient synthesis of quinazoline compounds.
Using iron-nitrogen co-doped carbon material catalyst, the catalyst uses nitrogen-doped carbon material as a support and supports iron element particles, including iron atoms and iron oxide forms, and is used to catalyze oxidize the synthesis of quinazole through specific preparation methods and reaction conditions. line and its derivatives.
It has achieved efficient and highly selective synthesis of quinazoline and its derivatives, with good stability and strong reusability, expanding the optional range of raw materials, good substrate tolerance and simple process.
Smart Images

Figure BDA0003714793550000041 
Figure BDA0003714793550000042 
Figure BDA0003714793550000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of synthesis of quinazoline and its derivatives, and in particular to an iron-nitrogen co-doped carbon material catalyst and application thereof in the synthesis of quinazoline and its derivatives. Background Art
[0002] Quinazoline and its derivatives have important biological activities and medicinal value. They are an important class of compounds with therapeutic properties such as anticancer, antiviral, anti-inflammatory and anticancer. In recent years, there are various methods and routes for preparing quinazoline. For example, quinazoline obtained by oxidation catalysis has moderate to excellent yields by reacting halogenated benzaldehydes and halogenated benzonitrile with amidine or guanidine as raw materials; however, quinazoline compounds contain two nitrogen atoms, and these two-component strategies may be affected by the unavailability of starting materials and the limited substrate range. In addition, the reaction of o-aminoaryl ketones with benzylamine is also an important means to synthesize quinazoline compounds, but it requires the presence of excess oxidants such as I2, CuO nanoparticles and 4-hydroxyTEMPO, tert-butyl hydroperoxide, etc. These catalysts and oxidants have more or less some obvious problems, such as low catalytic efficiency, poor reaction selectivity, harsh reaction conditions, high reaction cost, poor substrate tolerance, etc. Summary of the invention
[0003] The purpose of the present invention is to overcome one or more deficiencies of the prior art and to provide a novel iron-nitrogen co-doped carbon material catalyst for use in the synthesis of quinazoline and its derivatives, wherein the catalyst exhibits excellent catalytic performance for the synthesis of quinazoline and its derivatives, and is conducive to obtaining quinazoline and its derivatives with high efficiency and selectivity.
[0004] The present invention also provides the novel iron-nitrogen co-doped carbon material catalyst mentioned above.
[0005] In order to achieve the above object, a technical solution adopted by the present invention is:
[0006] An application of an iron-nitrogen co-doped carbon material catalyst in the catalytic oxidation synthesis of quinazoline and its derivatives, wherein the iron-nitrogen co-doped carbon material catalyst uses a nitrogen-doped carbon material as a carrier, and the carrier carries iron element particles, and the iron element particles are at least iron atoms (Fe 0 ) and iron oxide (FeO x ) forms exist simultaneously.
[0007] According to some preferred aspects of the present invention, the iron element particles exist in the form of iron atoms and iron oxide at the same time.
[0008] According to some preferred and specific aspects of the present invention, the iron oxide is ferric oxide.
[0009] According to some preferred aspects of the present invention, the iron atoms and the iron oxide are both nanometer-sized.
[0010] According to some preferred and specific aspects of the present invention, the preparation method of the iron-nitrogen co-doped carbon material catalyst includes: dispersing graphite-like carbon nitride (g-C3N4), chitosan and heme iron in a first solvent, mixing, removing the first solvent to obtain a solid intermediate, and then calcining under a protective atmosphere.
[0011] According to some preferred aspects of the present invention, during the preparation of the iron-nitrogen co-doped carbon material catalyst, the mass ratio of the graphite-like carbon nitride, the chitosan and the heme iron is 5-15: 0.5-2.5: 1. Further, the mass ratio of the graphite-like carbon nitride, the chitosan and the heme iron is 8-12: 1-1.5: 1.
[0012] According to some preferred aspects of the present invention, during the preparation of the iron-nitrogen co-doped carbon material catalyst, the first solvent is an alcohol solvent, which is a C1-C6 alcohol compound. In some embodiments of the present invention, the first solvent may be ethanol, propanol, or the like.
[0013] According to some preferred aspects of the present invention, during the preparation of the iron-nitrogen co-doped carbon material catalyst, the mixing is performed at room temperature by stirring and / or ultrasound.
[0014] According to some preferred aspects of the present invention, during the preparation of the iron-nitrogen co-doped carbon material catalyst, the solid intermediate is kept in a dry state before being calcined.
[0015] According to some preferred aspects of the present invention, during the preparation of the iron-nitrogen co-doped carbon material catalyst, the calcination is carried out at a calcination temperature of 750-850°C, which is more conducive to obtaining a catalyst of the expected structure and has a better catalytic oxidation effect on quinazoline and its derivatives.
[0016] According to some preferred aspects of the present invention, during the preparation of the iron-nitrogen co-doped carbon material catalyst, the heating rate from room temperature to the calcination temperature is controlled to be 4-6°C / min during the calcination process.
[0017] According to some preferred aspects of the present invention, during the preparation of the iron-nitrogen co-doped carbon material catalyst, the calcination time is controlled to be 1-3 hours.
[0018] In some embodiments of the present invention, during the preparation of the iron-nitrogen co-doped carbon material catalyst, the protective gas selected for the protective atmosphere is nitrogen, argon, etc.
[0019] In some embodiments of the present invention, the method for preparing the iron-nitrogen co-doped carbon material catalyst is as follows:
[0020] (1) dispersing graphite-like carbon nitride, chitosan and heme iron in ethanol to form a mixed solution;
[0021] (2) sonicating the mixed solution and stirring overnight;
[0022] (3) rotary evaporating the intermediate obtained in step (2) and drying it to obtain a solid powder;
[0023] (4) further drying the solid powder obtained in step (3);
[0024] (5) calcining the dried powder obtained in step (4) under a protective atmosphere to prepare the iron-nitrogen co-doped carbon material catalyst, which can be referred to as Fe-FeO x @NC (where Fe and FeO x represents the existence form of iron element particles, and NC represents nitrogen-doped carbon material).
[0025] In some embodiments of the present invention, in step (4), drying is performed at 55-65° C. for 10-14 hours.
[0026] In some embodiments of the present invention, in step (5), the calcination is carried out in a tubular furnace.
[0027] According to some preferred aspects of the present invention, in the application of synthesizing quinazoline and its derivatives, an aromatic o-aminocarbonyl compound, an alcohol compound, and aqueous ammonia are subjected to a catalytic oxidation reaction in a second solvent in the presence of an oxidant and an iron-nitrogen co-doped carbon material catalyst to generate quinazoline and its derivatives.
[0028] According to some preferred aspects of the present invention, the oxidant is oxygen, which is provided by introducing pure oxygen gas with a purity greater than 99% or air into the reaction system.
[0029] According to some preferred aspects of the present invention, the second solvent comprises water. In some embodiments of the present invention, the second solvent can be water.
[0030] According to some preferred aspects of the present invention, the molar ratio of the aromatic o-aminocarbonyl compound, the alcohol compound, and the ammonia in the ammonia water is 1:2-4:6-10. Further, the molar ratio of the aromatic o-aminocarbonyl compound, the alcohol compound, and the ammonia in the ammonia water is 1:2.5-3.5:7-9.
[0031] In some embodiments of the present invention, the ammonia water can be obtained commercially, and commercially available industrial ammonia water can be used, and the concentration thereof is about 25%-28%.
[0032] According to some preferred aspects of the present invention, the amount of the iron-nitrogen co-doped carbon material catalyst is 5%-65% of the amount of the aromatic o-aminocarbonyl compound added, calculated as a percentage by mass.
[0033] According to some preferred aspects of the present invention, the catalytic oxidation reaction is carried out under heating conditions. Further, the catalytic oxidation reaction is carried out at 100-150° C., and further at 120-140° C. According to a specific aspect of the present invention, the catalytic oxidation reaction is carried out at 130° C.
[0034] According to a specific aspect of the present invention, the catalytic oxidation reaction can be carried out in a sealed reactor in the presence of air.
[0035] According to some preferred aspects of the present invention, the aromatic o-aminocarbonyl compound has a structure shown in formula (I): In formula (I), n is 0, 1, 2, 3 or 4, R1 is H, F, Br, Cl, nitro, cyano, unsubstituted or substituted C1-C6 alkyl, R2 is H, unsubstituted or substituted C1-C6 alkyl, unsubstituted or substituted C6-C12 aryl, -NH-R4, and R4 is unsubstituted or substituted C1-C6 alkyl; wherein the substituent in the substituted C1-C6 alkyl is a combination of one or more selected from F, Br, Cl, nitro, cyano, and C1-C6 alkoxy, and the substituent in the substituted C6-C12 aryl is a combination of one or more selected from F, Br, Cl, nitro, cyano, C1-C6 alkoxy, and halogenated C1-C6 alkyl.
[0036] In some embodiments of the present invention, n is 0 or 1. When n is 1, R1 is substituted at the para position of the amino group.
[0037] Furthermore, R2 is methyl, ethyl, H, phenyl or halogenated phenyl.
[0038] According to some preferred aspects of the present invention, the alcohol compound has a structure shown in formula (II): In formula (II), R3 is an unsubstituted or substituted group as follows: phenyl, naphthyl, thienyl, Pyridyl, wherein the substituent used is a combination of one or more selected from the following groups: F, Br, Cl, nitro, cyano, C1-C6 alkyl, phenyl, C1-C6 alkoxy, halogenated C1-C6 alkyl.
[0039] Furthermore, among the optional groups of R3, the substitution positions of naphthyl, thienyl and pyridyl are as follows:
[0040] In the present invention, the C1-C6 alkyl group can be methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, n-pentyl, isopentyl, hexyl, etc.; the halogen selected for halogenation can be fluorine, chlorine or bromine; the C1-C6 alkoxy group can be methoxy, ethoxy, propoxy, isopropoxy, n-butoxy, isobutoxy, etc.
[0041] According to the present invention, the iron-nitrogen co-doped carbon material catalyst is used in the catalytic oxidation synthesis of quinazoline and its derivatives, and is recovered and reused after the reaction is completed, and can be reused multiple times without obvious attenuation of catalytic activity.
[0042] In some embodiments of the present invention, after the catalytic oxidation reaction is completed, ethyl acetate is added to the reaction mixture, and the organic phase and ethyl acetate are removed by rotary evaporation to obtain a crude product. Finally, a pure product is obtained by silica gel column chromatography.
[0043] In some embodiments of the present invention, the quinazoline and its derivatives have a structure shown in the following formula (III):
[0044] Wherein, R1, R2, R3 and n are the same as above.
[0045] In the present invention, quinazoline and its derivatives are synthesized in a one-pot method using the catalyst of the present invention, which is more green and efficient, has good reusability, and is conducive to large-scale production.
[0046] Another technical solution provided by the present invention is: an iron-nitrogen co-doped carbon material catalyst, which uses a nitrogen-doped carbon material as a carrier, and the carrier is loaded with iron particles, and the iron particles exist at least in the form of iron atoms and iron oxide.
[0047] In the present invention, the iron-nitrogen co-doped carbon material catalyst is in the form of an iron-nitrogen co-doped porous carbon material.
[0048] Another technical solution provided by the present invention is a method for preparing an iron-nitrogen co-doped carbon material catalyst, the preparation method comprising: dispersing graphite-like carbon nitride (g-C3N4), chitosan and heme iron in a first solvent, mixing, removing the first solvent to obtain a solid intermediate, and then calcining under a protective atmosphere.
[0049] In the present invention, graphite-like carbon nitride (g-C3N4) and chitosan can respectively play the role of supporting and stabilizing the catalyst in the catalyst, which is conducive to obtaining a catalyst with uniformly dispersed iron particles, and the formed nitrogen-doped carbon material can fix or coat iron atoms and FeOx Particles.
[0050] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0051] The present invention is based on the deficiencies in the prior art of catalytic oxidation synthesis of quinazoline and its derivatives. After a large number of experimental studies, it is found that by using an iron-nitrogen co-doped carbon material, taking the nitrogen-doped carbon material as a carrier, and loading iron element particles on the carrier, and the iron element particles at least co-existing in the form of iron atoms and iron oxide, when applied to the process of catalytic oxidation synthesis of quinazoline and its derivatives, quinazoline and its derivatives can be obtained with high efficiency and selectivity, and the stability is good, the reusability is good, the process is simple, the requirements for raw materials are low, the optional range of raw materials is expanded, and the substrate tolerance is good. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is a SEM image of the iron-nitrogen co-doped carbon material catalyst prepared in Example 1 of the present invention;
[0053] Figure 2 This is a TEM image of the iron-nitrogen co-doped carbon material catalyst prepared in Example 1 of the present invention;
[0054] Figure 3 This is the XRD pattern of the iron-nitrogen co-doped carbon material catalyst prepared in Example 1 of the present invention;
[0055] Figure 4 This is the XPS graph of the iron-nitrogen co-doped carbon material catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0056] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.
[0057] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art.
[0058] g-C3N4 was prepared by raising the temperature of melamine to 550°C at a rate of 5°C / min under a nitrogen atmosphere and then continuing to calcine for 2 hours; chitosan was purchased from Aladdin, with a specification of 100g and a product number of C105802-100g; heme iron was purchased from McLean, with a specification of 100g and a product number of H885986.
[0059] Example 1 Catalyst Fe-FeO x Preparation of @NC
[0060] This example provides a method for preparing an iron-nitrogen co-doped carbon material catalyst, and the method for preparing an iron-nitrogen co-doped carbon material catalyst comprises the following steps:
[0061] (1) g-C3N4, chitosan and heme iron in a mass ratio of 10:1.2:1 were dissolved in anhydrous ethanol to prepare a mixed solution, and ultrasonicated for 3 hours at room temperature; then, the anhydrous ethanol was removed by rotary evaporation after stirring overnight for 24 hours; and then, the solid powder was obtained by drying at 60°C for 12 hours.
[0062] (2) The solid powder obtained in step (1) was calcined in a tubular furnace at 800° C. for 2 h (heating rate of 5° C. / min) under a nitrogen atmosphere to obtain a granular carbon material catalyst in the form of an iron-nitrogen co-doped porous carbon material, i.e., an iron-nitrogen co-doped carbon material catalyst, denoted as Fe-FeO x @NC (where Fe and FeO x The obtained iron-nitrogen co-doped carbon material catalyst was tested as follows. The SEM, TEM, XRD and XPS images are shown in Figures 1 and 2. Figure 1 , Figure 2 , Figure 3 and Figure 4 The SEM image shows that the carbon material exists in a state of irregular aggregation; the TEM image shows that the carbon material contains nitrogen-doped carbon layers that wrap nano-iron particles, which are evenly distributed on the carbon material; the TEM and XRD images confirm that there may be Fe in the iron particles. 0 and Fe2O3 and other valence states; the XPS diagram illustrates the possible existence states of iron and nitrogen elements (valence state and chemical state, etc.).
[0063] Example 2
[0064] This example provides a method for preparing an iron-nitrogen co-doped carbon material catalyst, and the method for preparing an iron-nitrogen co-doped carbon material catalyst comprises the following steps:
[0065] (1) g-C3N4, chitosan and heme iron in a mass ratio of 10:1.5:1 were dissolved in anhydrous ethanol to prepare a mixed solution, and ultrasonicated for 3 hours at room temperature; then, the anhydrous ethanol was removed by rotary evaporation after stirring overnight for 24 hours; and then, the solid powder was obtained by drying at 60°C for 12 hours.
[0066] (2) The solid powder obtained in step (1) is calcined at 800°C for 2 h in a tubular furnace under a nitrogen atmosphere (heating rate of 5°C / min) to obtain a granular carbon material catalyst in the form of an iron-nitrogen co-doped porous carbon material, i.e., an iron-nitrogen co-doped carbon material catalyst.
[0067] Example 3
[0068] This example provides a method for preparing an iron-nitrogen co-doped carbon material catalyst, and the method for preparing an iron-nitrogen co-doped carbon material catalyst comprises the following steps:
[0069] (1) g-C3N4, chitosan and heme iron in a mass ratio of 12:1.2:1 were dissolved in anhydrous ethanol to prepare a mixed solution, and ultrasonicated for 3 hours at room temperature; then, the anhydrous ethanol was removed by rotary evaporation after stirring overnight for 24 hours; and then, the solid powder was obtained by drying at 60°C for 12 hours.
[0070] (2) The solid powder obtained in step (1) is calcined at 820°C for 2 h in a tubular furnace under a nitrogen atmosphere (heating rate of 5°C / min) to obtain a granular carbon material catalyst in the form of an iron-nitrogen co-doped porous carbon material, i.e., an iron-nitrogen co-doped carbon material catalyst.
[0071] Comparative Example 1
[0072] The method is basically the same as Example 1, except that step (1) is different. The specific steps are as follows:
[0073] (1) g-C3N4 and chitosan in a mass ratio of 10:1.2 were dispersed in anhydrous ethanol to form a mixed solution, and ultrasonicated at room temperature for 3 hours; then, the anhydrous ethanol was removed by rotary evaporation after stirring overnight for 24 hours; and then, it was dried at 60°C for 12 hours to obtain a solid powder.
[0074] (2) The solid powder obtained in step (1) was calcined at 800°C for 2 h in a tubular furnace under a nitrogen atmosphere (heating rate of 5°C / min) to obtain a granular carbon material catalyst in the form of an iron-nitrogen co-doped porous carbon material, denoted as NC (wherein NC represents nitrogen-doped carbon material).
[0075] Comparative Example 2
[0076] The same as Example 1, except that: x After the preparation of @NC, Fe-FeO without iron particles was prepared by pickling with 1 mol / L hydrochloric acid. x @NC-A (where Fe and FeO x represents the existence form of iron particles, NC represents nitrogen-doped carbon material, and A represents the pickling process).
[0077] Comparative Example 3
[0078] The method is basically the same as Example 1, except that: in step (1), heme iron is replaced by ferric nitrate nonahydrate (the mass of ferric nitrate is controlled to be the same as that of heme iron).
[0079] Example 4-28 Preparation of Quinazoline and Its Derivatives
[0080] 0.25 mmol of an aromatic o-aminocarbonyl compound with the structure shown in Table 1, 0.75 mmol of an alcohol compound, 2 mmol of ammonia water (commercially available industrial ammonia water, with a concentration of about 26.5±1.5%), 20 mg of Fe-FeO prepared in Example 1 were added. x @NC, 1 mL of water was added to the reaction vessel, heated to about 130 ° C under air conditions, and sealed for reaction for 24 hours. After the reaction was completed and cooled, the catalyst and the reaction liquid were centrifuged to separate. The reaction yield and selectivity were determined by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS). Fe-FeO x @NC, the organic phase was removed by rotary evaporation to obtain a crude product. Finally, the pure product was obtained by simple silica gel column chromatography. The specific results are shown in Table 1.
[0081] Application Comparative Example 1
[0082] The same as Example 4, except that the Fe-FeO prepared in Example 1 x @NC" was replaced by the catalyst NC prepared in Comparative Example 1. The specific results are shown in Table 1.
[0083] Application Comparative Example 2
[0084] The same as Example 4, except that the Fe-FeO prepared in Example 1 x @NC" was replaced by the catalyst Fe-FeO prepared in Comparative Example 2 x @NC-A. The specific results are shown in Table 1.
[0085] Application Comparative Example 3
[0086] The same as Example 4, except that the Fe-FeO prepared in Example 1 x @NC" was replaced by the catalyst prepared in Comparative Example 3. The specific results are shown in Table 1.
[0087] Table 1
[0088]
[0089]
[0090]
[0091]
[0092]
[0093] Embodiment 29:
[0094] Aromatic o-aminocarbonyl compounds 0.25mmol, alcohol compounds 0.75mmol, ammonia water (commercial industrial ammonia water, concentration is about 26.5±1.5%) 2mmol, 20mg of the catalyst prepared by Example 2, 1mL of water are added to the reaction container, heated to about 130°C under air conditions and sealed for reaction for 24 hours, after the reaction is completed and cooled, the catalyst and the reaction liquid are centrifuged, and the reaction yield and selectivity are determined by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS), the catalyst is centrifuged, and the organic phase is removed by rotary evaporation to obtain a crude product. Finally, the pure product is obtained by simple silica gel column chromatography. The yield is 92%.
[0095] Embodiment 30:
[0096] Aromatic o-aminocarbonyl compounds 0.25mmol, alcohol compounds 0.75mmol, ammonia water (commercial industrial ammonia water, concentration is about 26.5±1.5%) 2mmol, 20mg of the catalyst prepared by Example 3, 1mL of water are added to the reaction container, heated to about 130°C under air conditions and sealed for reaction for 24 hours, after the reaction is completed and cooled, the catalyst and the reaction liquid are centrifuged, and the reaction yield and selectivity are determined by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS), the catalyst is centrifuged, and the organic phase is removed by rotary evaporation to obtain a crude product. Finally, the pure product is obtained by simple silica gel column chromatography. The yield is 90%.
[0097] Example 31: Catalyst Reuse Activity Test
[0098] Aromatic o-aminocarbonyl compounds 0.25mmol, alcohol compounds 0.75mmol, ammonia water (commercial industrial ammonia water, concentration is about 26.5±1.5%) 2mmol, 20mg Fe-FeO prepared in Example 1 x @NC, 1 mL of water was added to the reaction vessel, heated to about 130 ° C under air conditions and sealed for reaction for 12 hours (Note: The reaction time of the recovery experiment is short, so the yield is low. The recovery effect under low yield conditions can better illustrate the recyclability of the catalyst). After the reaction is completed and the temperature is lowered, the catalyst and the reaction liquid are separated by centrifugation. The reaction yield and selectivity are determined by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS). The Fe-FeO x@NC was used as the catalyst for the next batch of the same reaction. The yields of the reactions of fresh use and 1-5 times use were as follows: 67%, 64%, 67%, 64%, 55%, 51%, respectively, and there was no obvious attenuation of the catalyst activity.
[0099] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
[0100] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
Claims
1. Application of an iron-nitrogen co-doped carbon material catalyst in the catalytic oxidation synthesis of quinazoline and its derivatives, It is characterized in that The iron-nitrogen co-doped carbon material catalyst uses a nitrogen-doped carbon material as a carrier, and the carrier carries iron element particles, and the iron element particles exist at least in the form of iron atoms and iron oxide; The preparation method of the iron-nitrogen co-doped carbon material catalyst comprises: dispersing graphite-like carbon nitride, chitosan and heme iron in a first solvent, mixing, removing the first solvent, obtaining a solid intermediate, and then calcining under a protective atmosphere, wherein the calcination is performed at a calcination temperature of 750-850° C.; In the application, an aromatic o-aminocarbonyl compound, an alcohol compound, and aqueous ammonia are subjected to a catalytic oxidation reaction in the presence of an oxidant and an iron-nitrogen co-doped carbon material catalyst in a second solvent to generate quinazoline and its derivatives; The aromatic o-aminocarbonyl compound has a structure shown in formula (I): In formula (I), n is 0, 1, 2, 3 or 4, R 1 is H, F, Br, Cl, nitro, cyano, unsubstituted or substituted C1-C6 alkyl, R 2 is H, unsubstituted or substituted C1-C6 alkyl, unsubstituted or substituted C6-C12 aryl, -NH-R 4 , R 4 is an unsubstituted or substituted C1-C6 alkyl group; wherein the substituent in the substituted C1-C6 alkyl group is a combination of one or more selected from F, Br, Cl, nitro, cyano, and C1-C6 alkoxy groups, and the substituent in the substituted C6-C12 aryl group is a combination of one or more selected from F, Br, Cl, nitro, cyano, C1-C6 alkoxy groups and halogenated C1-C6 alkyl groups; The alcohol compound has a structure shown in formula (II): In formula (II), R 3 is unsubstituted or substituted as follows: phenyl, naphthyl, thienyl, Pyridyl, wherein the substituent used is a combination of one or more selected from the following groups: F, Br, Cl, nitro, cyano, C1-C6 alkyl, phenyl, C1-C6 alkoxy, halogenated C1-C6 alkyl; The quinazoline and its derivatives have a structure shown in the following formula (III): Among them, R 1 , R 2 , n are respectively defined as in formula (I), R 3 Same as defined in formula (II).
2. Use of the iron-nitrogen co-doped carbon material catalyst according to claim 1 in the catalytic oxidation synthesis of quinazoline and its derivatives, It is characterized in that The iron oxide is ferric oxide; and / or the iron element particles exist in the form of iron atoms and iron oxide at the same time.
3. Use of the iron-nitrogen co-doped carbon material catalyst according to claim 1 in the catalytic oxidation synthesis of quinazoline and its derivatives, It is characterized in that The iron atoms and the iron oxide are both in nanometer size.
4. Use of the iron-nitrogen co-doped carbon material catalyst according to claim 1 in catalytic oxidation synthesis of quinazoline and its derivatives, It is characterized in that The mass ratio of the graphite-like carbon nitride, the chitosan and the heme iron is 5-15:0.5-2.5:
1.
5. Use of the iron-nitrogen co-doped carbon material catalyst according to claim 1 in catalytic oxidation synthesis of quinazoline and its derivatives, It is characterized in that The first solvent is an alcohol solvent, and the alcohol solvent is a C1-C6 alcohol compound; and / or, the mixing is performed at room temperature, using stirring and / or ultrasound.
6. Use of the iron-nitrogen co-doped carbon material catalyst according to claim 1 in catalytic oxidation synthesis of quinazoline and its derivatives, It is characterized in that The solid intermediate is kept in a dry state before being calcined.
7. Use of the iron-nitrogen co-doped carbon material catalyst according to claim 1 in catalytic oxidation synthesis of quinazoline and its derivatives, It is characterized in that During the calcination process, the heating rate from room temperature to the calcination temperature is controlled to be 4-6°C / min; and / or the calcination time is controlled to be 1-3h.
8. Use of the iron-nitrogen co-doped carbon material catalyst according to claim 1 in catalytic oxidation synthesis of quinazoline and its derivatives, It is characterized in that The oxidant is oxygen, which is provided by introducing pure oxygen gas with a purity greater than 99% or air into the reaction system; and / or the second solvent comprises water.
9. Use of the iron-nitrogen co-doped carbon material catalyst according to claim 1 in catalytic oxidation synthesis of quinazoline and its derivatives, It is characterized in that The molar ratio of the aromatic o-aminocarbonyl compound, the alcohol compound and the ammonia in the ammonia water is 1:2-4:6-10; and / or, in terms of mass percentage, the amount of the iron-nitrogen co-doped carbon material catalyst is 5%-65% of the amount of the aromatic o-aminocarbonyl compound added.
10. Use of the iron-nitrogen co-doped carbon material catalyst according to claim 1 in catalytic oxidation synthesis of quinazoline and its derivatives, It is characterized in that The catalytic oxidation reaction is carried out under heating conditions.
11. An iron-nitrogen co-doped carbon material catalyst, Features: The iron-nitrogen co-doped carbon material catalyst uses a nitrogen-doped carbon material as a carrier, and the carrier carries iron element particles, and the iron element particles exist at least in the form of iron atoms and iron oxide; The preparation method of the iron-nitrogen co-doped carbon material catalyst comprises: dispersing graphite-like carbon nitride, chitosan and heme iron in a first solvent, mixing, removing the first solvent, obtaining a solid intermediate, and then calcining under a protective atmosphere, wherein the calcination is carried out at a calcination temperature of 750-850° C., and the feed mass ratio of the graphite-like carbon nitride, the chitosan and the heme iron is 5-15:0.5-2.5:1.
